Triggers and Conditions for Innovations in Dubai - Assalama, Iman (2009)
The dissertation was set out to get a thorough understanding of innovation in general, the different factors that may trigger the adoption of the innovation, and the conditions required in the organization to ensure the innovation’s success. The dissertation aims to enhance the level of innovation in the United Arab Emirates’ organizations, and specifically in Dubai’s organizations. This can be established through the understanding of the main triggers and conditions that are associated with successful innovations in Dubai’s organizations. Provided that innovation is claimed to survive organizations through tough market situations, this dissertation seemed timely due to the current global credit crunch crisis. Considering the importance of this topic and its different dimensions, mixed approach research was selected for this dissertation. The surveys and interviews were conducted concurrently to collect different information and data from both targeted populations. The findings of the dissertation revealed several external triggers for innovation in Dubai’s organizations, such as the client’s demand and the market conditions. The suggested internal triggers were management’s characteristics, and vision. The proposed organizational conditions that seemed associated with successful innovations were the organization’s culture, climate, structure, employee empowerment, and the allocation of innovation champion. On the one hand, Dubai’s organizations seemed to associate innovation significantly with the organization’s climate, staff empowerment, and the allocation of innovation champion. On the other hand, innovation in Dubai’s organizations seemed to be specifically dependent on the level of staff empowerment, and a positive organizational climate. The dissertation was concluded with a set of recommendations to improve the main organizational conditions that are associated with innovation. This included : guidelines on emplacing an appropriate staff empowerment, setting an “Enterprise Integration Group” to align the organizational climate with the organization’s direction, proposed different approaches on allocating innovation champions, and finally, additional recommendations included different suggestions on enhancing the organizational culture, management skills, and employee development.